Estimates of conformal maps of curvilinear strips - Gol’dberg, A. A. (Математическая физика, анализ, геометрия, 2002)
Distortion estimates for conformal maps of curvilinear strips are obtained. The upper estimate applies to much more general class of the strips than in Warschawski’s theorem.